OPTIMISM AND SOCIAL SUPPORT AS PREDICTORS OF ACADEMIC STRESS - Hidayat, Novi; Ikromi, Ziyadi Ali; Daswilah, Neulis Dewi Julaeha (Jurnal Agama Buddha dan Ilmu Pengetahuan, 2025)
Academic stress experienced by students is subject to a multitude of psychological and environmental determinants, including but not limited to optimism and social support. The present study endeavors to explore the predictive influences of optimism and social support on academic stress among junior high school students. A cohort of 80 students from junior high schools located in Banyumas, Central Java, Indonesia. was meticulously selected through a purposive sampling method. The participants were required to complete three standardized assessment tools: the Academic Stress Scale, the Optimism Scale, and the Social Support Scale. Each assessment tool underwent validation through content validity (item-total correlation > 0.30) and exhibited commendable reliability, with Cronbach's Alpha coefficients registering at 0.806 for academic stress, 0.791 for optimism, and 0.772 for social support. The data were subjected to analysis via multiple regression techniques, employing a significance threshold of 0.05. The findings indicated that both optimism and social support serve as significant predictors of academic stress levels. In particular, elevated levels of optimism and perceived social support were correlated with diminished academic stress. levels of academic stress. These findings underscore the importance of fostering optimism and strengthening social support systems to mitigate academic stress in adolescents